Crystal structure of human nicotinic acid phosphoribosyltransferase. Issue 1 (7th May 2015) - Marletta, Ada Serena; Massarotti, Alberto; Orsomando, Giuseppe; Magni, Giulio; Rizzi, Menico; Garavaglia, Silvia
Abstract : Nicotinic acid phosphoribosyltransferase (EC 2.4.2.11) (NaPRTase) is the rate‐limiting enzyme in the three‐step Preiss–Handler pathway for the biosynthesis of NAD. The enzyme catalyzes the conversion of nicotinic acid (Na) and 5‐phosphoribosyl‐1‐pyrophosphate (PRPP) to nicotinic acid mononucleotide (NaMN) and pyrophosphate (PPi). Several studies have underlined the importance of NaPRTase for NAD homeostasis in mammals, but no crystallographic data are available for this enzyme from higher eukaryotes. Here, we report the crystal structure of human NaPRTase that was solved by molecular replacement at a resolution of 2.9 Å in its ligand‐free form. Our structural data allow the assignment of human NaPRTase to the type II phosphoribosyltransferase subfamily and reveal that the enzyme consists of two domains and functions as a dimer with the active site located at the interface of the monomers. The substrate‐binding mode was analyzed by molecular docking simulation and provides hints into the catalytic mechanism. Moreover, structural comparison of human NaPRTase with the other two human type II phosphoribosyltransferases involved in NAD biosynthesis, quinolinate phosphoribosyltransferase and nicotinamide phosphoribosyltransferase, reveals that while the three enzymes share a conserved overall structure, a few distinctive structural traits can be identified. In particular, we show that NaPRTase lacks a tunnel that, in nicotinamide phosphoribosiltransferase, represents the binding site of its potent and selective inhibitor FK866, currently used in clinical trials as an antitumoral agent. Abstract : Human NaPRTase is a functional dimer. The structural bases for FK866 lack of inhibition of human NaPRTas were identified. Na, Nam and QA phosphoribosyltransferases share a conserved fold. Na, Nam and QA phosphoribosyltransferases show distinctive traits in the active site. Human and Enterococcus faecalis NaPRTase are highly structurally conserved.